Factors Related to Anemia Prevention in Adolescent Females at Baitul Jannah Islamic High School in Bandar Lampung in 2025 - Azzahra Kania Fatihah; Christin Angelina Febriani; Nurul Aryastuti; Nova Muhani (PROMOTOR, 2026)
The prevalence of anemia among adolescent girls in Indonesia remains high, reaching 84.6%, with Lampung Province having the highest prevalence in Sumatra at 63%. The government's iron supplementation program has not yet reached its target, reaching only 81.16% of the 95% target. A pre-survey at Baitul Jannah Islamic High School (SMA IT) showed that 66.6% of female students are anemic. This study aims to determine factors associated with anemia prevention in adolescent girls at the school by 2025. This study used a quantitative method with a cross-sectional design conducted at SMA IT Baitul Jannah Bandar Lampung from October 2024 to July 2025. The population consisted of 94 female students in grades X and XI, with a sample of 84 students determined using the Slovin formula and purposive sampling technique. Independent variables included knowledge, attitudes, and family support, while the dependent variable was anemia prevention efforts. Data were collected through questionnaires that had been tested for validity and reliability, then analyzed univariately and bivariately using the chi-square test. The results of the study revealed no relationship between knowledge (p-value = 0.192), attitude (p-value = 0.694), and family support (p-value = 0.041 and OR = 3.750) with anemia prevention efforts in adolescent girls. Schools can conduct routine education about anemia by inviting health workers to students, teachers, parents, and school officials with interesting media.